Literary Journalism across the Globe - John S. Bak, Bill Reynolds (University of Massachusetts Press, 2011)
At the end of the nineteenth century, several countries were developing journalistic traditions similar to what we identify today as literary journalism or literary reportage. Throughout most of the twentieth century, however, and in particular after World War I, that tradition was overshadowed and even marginalized by the general perception among democratic states that journalism ought to be either â€œobjective,â€ as in the American tradition, or â€œpolemical,â€ as in the European one. Nonetheless, literary journalism would survive and at times even thrive. How and why is a story unique to each nation. While many students, scholars, and practitioners of literary journalism have long acknowledged the formâ€™s Anglo-American roots, this book takes a broader approach to examining the ways literary journalism has been practiced and read throughout the world. From China to Brazil, Scotland to Australia, and Finland to New Zealand, international literary journalism has established itself as one of the most significant and controversial forms of writing of the last centuryâ€”significant because it often raises our sociopolitical awareness about a disenfranchised or underprivileged people; controversial because its emphasis on authorial voice jeopardizes our faith in its claims of accuracy. In the age of electronic news, however, when concerns about word count and article length have almost become a thing of the past, literary journalism seems poised to revolutionize the way we read journalism and appreciate literature. This book aims to assess the extent to which literary journalism over the past century has influenced reporting in various nationsâ€”some of which have only recently known democracy, while others are still under full or partial state controlâ€”and how it might shape journalistic heuristics and literary aesthetics in the twenty-first century.